Heterotopic Pancreas: Overview and a Case Report - Ghanem, Muhammad; Alhanwt, Alaa (Recent Developments in Medicine and Medical Research Vol. 14, 2021)
Heterotopic pancreas (HP) is the presence of pancreatic tissue in anomalous location without any anatomic, vascular or neural continuity with the main body of the pancreas. HP is mostly located in the upper gastrointestinal tract. Most patients are asymptomatic. Epigastric pain is the most common symptom in symptomatic patients. It is rare to be diagnosed and accidentally discovered during surgery. EUS is a good way to study the structure of the submucosal lesions like HP. Patients without symptoms can be observed while symptomatic patients should have HP resected. We have a case of a female who had a chronic abdominal epigastric pain. Investigations revealed a submucosal mass which was diagnosed a HP. She had also sludge in the gallbladder. We performed local resection to resect HP totally from the stomach with clear margins laparoscopically as well as cholecystectomy in one procedure. Our patient was fully recovered. Objectives: -Overview of Heterotopic Pancreas (HP). -Study a case of pancreatic heterotopia mass in the stomach.